Digital Government and Covid 19: A Structured Literature Review - Sugeng Winarno; Salahudin; Muslimin Machmud (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2023)
The COVID-19 pandemic has hindered government performance. Therefore, innovation through the implementation and improvement of digital government is the primary key. The purpose of this study is to undertake a systematic review of published works on the subject of Digital Government. The purpose of this study is to ascertain the trend of studies on the development of digital government models conducted by numerous governments during the Covid-19 epidemic. This study does descriptive analysis on primary data gathered from the Scopus database under the keywords digital government and Covid-19 for the timeframe 2020-2021. The data is then processed and visualized with Vos-Viewer which shows that data, policy, health, innovation, effect and digital transformation are the most dominant concepts. These concepts are the dominant or massive focus previously studied. The contribution of this research is a reference for many countries to innovate internet-based public services to be more efficient and effective. This research is limited because the data source only comes from Scopus. Therefore, in order to produce a comparative, broad and comprehensive analysis, further studies need to include sources of other reputable international journals such as the Web of Science (WoS).